363. National Burden of Candidemia, United States, 2017. (26th November 2018) - Tsay, Sharon; Williams, Sabrina; Mu, Yi; Epson, Erin; Johnston, Helen; Farley, Monica M; Harrison, Lee H; Vonbank, Brittany; Shrum, Sarah; Dumyati, Ghinwa; Zhang, Alexia; Schaffner, William; et al.
Abstract: Background: Candidemia is a common healthcare-associated bloodstream infection associated with high morbidity and mortality. No current estimates exist for understanding its burden in the United States. Methods: In 2017, CDC's Emerging Infections Program (EIP) performed laboratory- and active population-based candidemia surveillance in 45 counties in nine states (California, Colorado, Georgia, Maryland, Minnesota, New Mexico, New York, Oregon, Tennessee), encompassing ~17 million persons. A case was defined as Candida species isolated from blood in a surveillance area resident. EIP site staff reviewed medical records to collect demographic and clinical data. Using 2016 US census data, we created weighted estimates of national and regional incidence rates and mortality in persons with candidemia (defined as death from any cause within 7 days of incident candidemia). Results: A total of 1, 226 candidemia cases were identified in 2017. We estimated 23, 000 candidemia cases (95% CI 20, 000–25, 000) occurred in the United States in 2017. Overall estimated incidence was 7.0/100, 000 persons, with elevated rates in adults ≥65 years (20.3/100, 000), males (8.0/100, 000), and people of Black race (12.6/100, 000) (table). Incidence was highest in the South Atlantic region (8.0/100, 000) and lowest in the Pacific (6.0/100, 000). Estimated number of deaths was 3, 000 (1, 000–5, 000). Conclusion: Our analysis highlights the substantial burden of candidemia in the US Because candidemia is only one form of invasive candidiasis, the true burden of invasive infections due to Candida species is likely higher. Ongoing surveillance can support future burden estimates and help assess the impact of prevention interventions. Disclosures: All authors: No reported disclosures.